2018
DOI: 10.1111/jasp.12501
|View full text |Cite
|
Sign up to set email alerts
|

A field study on watching eyes and hand hygiene compliance in a public restroom

Abstract: Humans modify their behavior in a socially desirable way when being watched by others. We applied this basic idea to hand hygiene compliance, a behavior that is crucial for preventing germ transmission and successive infections in many settings. Building on the assumption that hand hygiene behavior is socially desirable, we assume that individuals show stronger hand hygiene compliance when being watched. In a field study in a women's public restroom (N = 354), we exposed individuals to a message advising that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…These initiatives have often focused on behavioral changes that increase the environmental and social sustainability of their target contexts. Successful examples include both challenges directly related to environmental issues such as energy and water consumption [14,15], sustainable transport use [16,17], recycling [18,19] and food choices [20][21][22], as well as broader social sustainability issues such as alcohol consumption [23], hygiene [24,25], and harassment and violence [6,26].…”
Section: Introductionmentioning
confidence: 99%
“…These initiatives have often focused on behavioral changes that increase the environmental and social sustainability of their target contexts. Successful examples include both challenges directly related to environmental issues such as energy and water consumption [14,15], sustainable transport use [16,17], recycling [18,19] and food choices [20][21][22], as well as broader social sustainability issues such as alcohol consumption [23], hygiene [24,25], and harassment and violence [6,26].…”
Section: Introductionmentioning
confidence: 99%
“…Feeling observed and aware of our actions seems to be the factor that affects dishonesty. Furthermore, the simple presence of others can affect our behavior and performance in a task [20] and even just the presence of an image of a pair of eyes can make people feel more observed [28], and consequently, wash more their hands [30] or litter less in a cafeteria [13]. Studies also show that faces with direct gaze capture more our attention than avert gaze (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Having movable eyes on the robot was especially important in this context, as people change their behaviour when they know they're being watched ("Hawthorne Effect") [14]. Also a field study by Pfattheicher et al [15] showed a significant increase of hand hygiene compliance when watching eyes were presented in a restroom. The eye mechanism was 3D printed with PLA material from a design published under the creative commons [16] which has two degrees of freedom (in the yaw and pitch axes), with a range of -45 to +45 degrees in each axis.…”
Section: B Eye Designmentioning
confidence: 99%